Economic Profitability of Sweet Pepper Production under Different Irrigation Levels and Polyethylene Mulch in a Plastic Greenhouse - Abdrabbo, Mohamed A. A.; Mohamed, Assem A. A.; Hashem, Fadl. A.; Hegab, Ahmed. S. A. (Applied Studies in Agribusiness and Commerce, 2018)
Field experiment was conducted, during two successive seasons of 2014- 2015 and 2015- 2016, at Dokki protected agricultural site, Giza Governorate, Egypt, to study the profitability of different applied irrigation levels and polyethylene (PE) mulch on plant growth and yield of sweet pepper, (Capsicum annum L.) cv. Godion F1, under plastic house condition. Three irrigation levels (0.50, 0.75 and 1.00) of crop evapotranspiration (ETc), using drip irrigation system and three PE mulch treatments (transparent, black and control) were applied. Data revealed that black PE recorded the highest values of early and total fruit yield per plant during the two seasons. Increasing water level up to 1.00 (ETc) enhanced yield with different PE mulch treatments, while water use efficiency (WUE) decreased with increasing water level. However, Using 0.50 (ETc), with different PE mulches increased WUE compared to using 0.75 (ETc) or 1.00 (ETc). The economic assessment of costs and returns from different treatments were calculated. It was found that the average yield was higher in 1.00 ETc with black mulch. Gross margin per 540 m2 were analysed using yield data, price structures and production costs. The 1.00 (ETc) with black mulch had the highest gross margin which is USD 416.8 and USD 533 (1 USD= 9 Egyptian pound) for the first and second seasons, respectively. The benefit cost ratios (BCRs) per 540 m2 were analysed, and 1.00 (ETc) with black mulch had the highest BCR with 1.36 in the first season and 1.45 in the second season.JEL Classification: Q 01, Q 12, Q 19